The Proposed Molecular Mechanisms Used by Archaea for Fe(III) Reduction and Fe(II) Oxidation - Dong, Yiran; Shan, Yawei; Xia, Kemin; Shi, Liang (Frontiers in Microbiology, 2021)
Iron (Fe) is the fourth most abundant element in the Earth’s crust where ferrous Fe [Fe(II)] and ferric Fe [Fe(III)] can be used by archaea for energy conservation. In these archaea-Fe interactions, Fe(III) serves as terminal electron acceptor for anaerobic respiration by a variety of archaea, while Fe(II) serves as electron donor and/or energy sources for archaeal growth. As no Fe is incorporated into the archaeal cells, these redox reactions are referred to as dissimilatory Fe(III) reduction and Fe(II) oxidation, respectively. Dissimilatory Fe(III)-reducing archaea (FeRA) and Fe(II)-oxidizing archaea (FeOA) are widespread on Earth where they play crucial roles in biogeochemical cycling of not only Fe, but also carbon and sulfur. To reduce extracellular Fe(III) (oxyhydr)oxides, some FeRA transfer electrons directly to the Fe(III) (oxyhydr)oxides most likely via multiheme c-type cytochromes (c-Cyts). These multiheme c-Cyts may form the pathways similar to those found in bacteria for transferring electrons from the quinone/quinol pool in the cytoplasmic membrane to the Fe(III) (oxyhydr)oxides external to the archaeal cells. Use of multiheme c-Cyts for extracellular Fe(III) reduction by both Domains of Archaea and Bacteria emphasizes an ancient mechanism of extracellular electron transfer, which is well conserved. Other FeRA, however, reduce Fe(III) (oxyhydr)oxides indirectly via electron shuttles. Similarly, it is proposed that FeOA use pathways to oxidize Fe(II) on the surface of the cytoplasmic membrane and then to transfer the released electrons across the cytoplasmic membrane inward to the O2 and NAD+ in the cytoplasm. In this review, we focus on the latest understandings of the molecular mechanisms used by FeRA and FeOA for Fe(III) reduction and Fe(II) oxidation, respectively.